Effect of vitamin D supplementation on the incidence and prognosis of depression: An updated meta-analysis based on randomized controlled trials - Xie, Fei; Huang, Tongmin; Lou, Dandi; Fu, Rongrong; Ni, Chaoxiong; Hong, Jiaze; Ruan, Lingyan (Frontiers in Public Health, 2022)
Background: There have been several controversies about the correlation between vitamin D and depression. This study aimed to investigate the relationship between vitamin D supplementation and the incidence and prognosis of depression and to analyze the latent effects of subgroups including population and supplement strategy. Methods: A systematic search for articles before July 2021 in databases (PubMed, EMBASE, Web of Science, and the Cochrane Library) was conducted to investigate the effect of vitamin D supplementation on the incidence and prognosis of depression. Results: This meta-analysis included 29 articles with 4,504 participants, indicating that the use of vitamin D was beneficial to a decline in the incidence of depression (SMD: -0.23) and improvement of depression treatment (SMD: -0.92). Subgroup analysis revealed that people with low vitamin D levels (<50 nmol/L) and females could notably benefit from vitamin D in both prevention and treatment of depression. The effects of vitamin D with a daily supplementary dose of >2,800 IU and intervention duration of ≥8 weeks were considered significant in both prevention and treatment analyses. Intervention duration ≤8 weeks was recognized as effective in the treatment group. Conclusions: Our results demonstrate that vitamin D has a beneficial impact on both the incidence and the prognosis of depression. Whether suffering from depression or not, individuals with low vitamin D levels, dose >2,800 IU, intervention duration ≥8 weeks and all females are most likely to benefit from vitamin D supplementation.